Experimental architecture : designing the unknown - Armstrong, Rachel, 1966- (New York : Routledge, 2019)
In this ground-breaking book, the first to provide an overview of the theory and practice of experimental architecture, Rachel Armstrong explores how interdisciplinary, design-led research practices are beginning to redefine the possibilities of architecture as a profession. Drawing on experts from disciplines as varied as information technology, mathematics, poetry, graphic design, scenography, bacteriology, marine applied science and robotics, Professor Armstrong delineates original, cutting-edge architectural experiments through essays, quotes, poetry, equations and stories. Written by an acknowledged pioneer of architectural experiment, this visionary book is ideal for students and researchers wishing to engage in experimental, practice-based architectural and artistic research. It introduces radical new ideas about architecture and provides ideas and inspiration which students and researchers can apply in their own work and proposals, while practitioners can draw on it to transform their creative assumptions and develop thereby a distinctive "edge" to stand out in a highly competitive profession.
OCLC-licensed vendor bibliographic record.
Keywords: Architectural practice; Architecture -- Research; ARCHITECTURE / Adaptive Reuse & Renovation; ARCHITECTURE / Buildings / Landmarks & Monuments; ARCHITECTURE / Professional Practice; ARCHITECTURE / Reference; ARCHITECTURE / General; ARCHITECTURE / Criticism; ARCHITECTURE / Design & Drafting